Hubungan Gaya Hidup Dengan Hipertensi Pada Penjaga Wisata Di Pantai Sulamadaha Kota Ternate - Soesanti Soesanti; Abd Hakim Husen (NHM PRESS, 2022)
One of the non-communicable diseases that attack the community today is hypertension. Hypertension is often referred to as the silent killer because the conditions experienced by sufferers are generally asymptomatic and then only have meaning when they have reached the level of severe damage. Purpose This study aims to determine the relationship between exercise habits and smoking habits with hypertension in tourist guards on the Sulamadaha beach, Ternate City. Methods The type of research used is analytic observational with a cross sectional study design. Results From a total of 30 respondents there is a significant relationship between lifestyle and hypertension with p = 0.004 and p = 0.008 < = 0.05. Lifestyle is an important factor in the incidence of hypertension in a person, including young adults. The increase in hypertension is influenced by an unhealthy lifestyle in the form of a lack of exercise and smoking behavior.